The Role of Leadership in Enhancing Employee Engagement in Startups - Priadana, Sidik; Iryadana, Mohamad Razab (International Journal of Sharia Business Management, 2024)
This study aims to explore the role of leadership in increasing employee engagement in startups. The main focus of this study is to understand how different leadership styles affect employee motivation, commitment, and engagement in a dynamic and rapidly changing startup environment. The research method used is a quantitative approach using questionnaires distributed to employees from several different startups. The data collected were then analyzed using descriptive and inferential statistical techniques to identify the relationship between leadership styles and employee engagement levels. The results showed that transformational leadership has a significant impact on employee engagement, with elements such as inspiration and personal support playing an important role in increasing employee motivation and commitment. In contrast, transactional leadership styles showed a smaller influence on employee engagement in the startup context. The conclusion of this study is that transformational leadership can be the key to increasing employee engagement in startups. Startup companies are advised to adopt a more inspirational and supportive leadership style to create a more productive and committed work environment. This study provides valuable insights for startup leaders and human resource practitioners in designing effective leadership strategies to increase employee engagement.